Peran Anatomi dalam Pengenalan Penyakit Degeneratif pada Sistem Muskuloskeletal - Novrina Situmorang (Universitas Methodist Indonesia, 2024)
Degenerative musculoskeletal illnesses may be better understood and diagnosed with a firm grasp of human anatomy. Disc degeneration, osteoarthritis, and osteoporosis are degenerative illnesses that impact the body's ability to function, particularly in older individuals. The ability to accurately diagnose musculoskeletal disorders depends on medical professionals' in-depth familiarity of the normal anatomy and physiology of the musculoskeletal system. The purpose of this research is to better understand how accurate anatomy may aid in the diagnosis of degenerative illnesses at an early stage and how this understanding can inform the development of more efficient methods of prevention and therapy. New clinical approaches to the therapy of degenerative musculoskeletal illnesses may be illuminated by the findings of this investigation.